2011
DOI: 10.1126/science.1205216
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Genomic Profiling for Antimalarial Therapies, Response Signatures, and Molecular Targets

Abstract: Malaria remains a devastating disease largely because of widespread drug resistance. New drugs and a better understanding of the mechanisms of drug action and resistance are essential for fulfilling the promise of eradicating malaria. Using high-throughput chemical screening and genome-wide association analysis, we identified 32 highly active compounds and genetic loci and genes associated with differential chemical phenotypes (DCPs), defined as ≥5-fold differences in half-maximum inhibitor concentration (IC50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
135
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 41 publications
7
135
0
Order By: Relevance
“…Not surprisingly, drugs with similar chemical structures (e.g., halofantrine, lumefantrine, and mefloquine) show a strong correlation in responses (Fig. S2), as has previously been observed (6,7), and provide the opportunity for cross-validation of SNPs identified in association studies.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Not surprisingly, drugs with similar chemical structures (e.g., halofantrine, lumefantrine, and mefloquine) show a strong correlation in responses (Fig. S2), as has previously been observed (6,7), and provide the opportunity for cross-validation of SNPs identified in association studies.…”
Section: Resultssupporting
confidence: 66%
“…In P. falciparum, however, array-based GWAS is severely limited by the relatively short extent of LD (5)(6)(7)(8). Lacking that correlation between genetic markers, genotyping arrays usually cannot detect associations with untyped markers, effectively limiting inferences to markers actually present on the array; even the highest density P. falciparum array reported to date found that LD between adjacent markers on the array was too weak for tagging in African populations (6).…”
mentioning
confidence: 99%
“…Earlier GWAS using in vitro resistance phenotypes (16,17,19) found associations between SNPs in several genes and IC 50 of DHA and other artemisinin derivatives, but none were in our topranked signatures of selection or in LD windows corresponding to our GWAS hits. This discordance is likely explained by the use of different resistance phenotypes.…”
Section: Discussionmentioning
confidence: 62%
“…The complex parasite population structure observed in Cambodia cannot be explained by grouping parasites from the two Cambodian sites, which are in close geographic proximity, and the same structure patterns were observed within each site individually. Previous GWAS examining in vitro susceptibility to artemisinins have also noted multiple populations of parasites in Cambodia (16,17). This complex population structure in Cambodia warrants further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…7 Whether these effects are due to PfCRT-mediated drug efflux and/or the inhibition of the transporter's normal function (which is essential for the survival of the parasite, but currently unknown) remains unclear.…”
mentioning
confidence: 99%